2013
DOI: 10.1248/bpb.b13-00515
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antitumor Activities of Sepantronium Bromide (YM155), a Survivin Suppressant, in Combination with Microtubule-Targeting Agents in Triple-Negative Breast Cancer Cells

Abstract: Triple-negative breast cancer (TNBC) has a poor prognosis compared to other subtypes, and effective treatment options are limited to cytotoxic agents, including microtubule-targeting agents, due to the lack of molecular targets. Here, we examined the combined effect of sepantronium bromide (YM155) and microtubule-targeting agents in TNBC models. The combination of YM155 with docetaxel showed synergistic antiproliferative and caspase 3/7-inducing effects in MRK-nu-1 and MDA-MB-453 human TNBC cell lines in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
(38 reference statements)
1
7
0
1
Order By: Relevance
“…In previous studies, it was demonstrated that tumor regression induced by YM155 in combination with docetaxel was accompanied by a decrease in intratumoral survivin and an increase in apoptosis rate. These results support the conclusion that survivin inhibition might be an effective way to enhance the efficacies of microtubule-targeting agents against TNBC [56] .…”
Section: Triple Negative Breast Cancer and Chemotherapy Enhanced By Ssupporting
confidence: 86%
“…In previous studies, it was demonstrated that tumor regression induced by YM155 in combination with docetaxel was accompanied by a decrease in intratumoral survivin and an increase in apoptosis rate. These results support the conclusion that survivin inhibition might be an effective way to enhance the efficacies of microtubule-targeting agents against TNBC [56] .…”
Section: Triple Negative Breast Cancer and Chemotherapy Enhanced By Ssupporting
confidence: 86%
“…Based on above, we predicate that survivin inhibitor may have synergic effects with traditional chemoreagents, such as platiums and taxanes, in HNSCC, which have been proven by previous studies and preclinical researches in various cancers. 15 , 40 , 41 , 42 Therefore, we examined the synergistic effects of YM155 combined with docetaxel in HNSCC using xenograft models. Results showed that YM155 combined with docetaxel exhibited better antitumor effects than either chemoreagent alone without additional toxicity, showing synergistic effects on HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies demonstrated that inhibition of apoptosis by survivin required interaction with microtubules [ 18 ], providing a powerful rationale for the study of survivin together with anti-microtubule agents such as taxanes. YM155 in combination with the microtubule-targeted agent docetaxel induced greater apoptosis compared with either agent alone, resulting in complete tumor regression in a mouse TNBC xenograft model [ 19 ]. The results of a phase I study indicated that YM155 was well tolerated with manageable toxicities in patients with advanced solid tumors, including breast cancer, that were refractory to standard therapy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%